FRANCHISING IN ORGANIZED RETAIL IN HARYANA: ISSUES AND OPPORTUNITIES (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2026)
The robust economy of Haryana, along with steadily increasing levels of consumer demand, translates to significant new business potential for retail franchises. This paper investigates the potential and difficulties in depth, thereby providing insights into the changing environment of organized retail in Haryana. Results highlight the main issues faced by the organized sector, specifically in the five districts of Haryana: Ambala, Faridabad, Gurugram, Kurukshetra, and Panchkula. Data have been collected from a sample of 320 respondents of different age groups for the investigation of the study. From the results, it has been found that at 0.86, brand reputation and training and support are favorably connected. Famous brands train and aid franchisees more, where a high brand reputation aligns with comprehensive training. Marketing assistance and brand reputation are positively associated (0.89). High correlations between territory protection and high royalty fees (0.77) suggest that territory protection is linked to higher royalty fees. The R-squared of 0.69 suggests the model explains many franchising fluctuations. This high F-value indicates that the model is statistically significant, with an F-statistic of 116.24. Research indicates that brand reputation, training and support, and territory protection improve franchising model effectiveness. However, large royalty payments and statistically significant disputes hurt franchising. It highlights the necessity of adopting a strategic and flexible approach in order to succeed in an ever-changing industry. According to the findings of the study, there is great potential for franchising in Haryana’s organized retail sector. This, however, is contingent upon franchisors being able to manage the difficulties and effectively engage with local partners.
Keywords: Franchisors; Foreign Direct; Investment (FDI); Information; Technology (IT); Indian Enterprises; Organized Sector; Retailers